International management : - Deresky, Helen (Pearson Prentice Hall, 2006)
This globally oriented book covers the most current research and trends in International Management. It offers comprehensive and integrative cases that illustrate the actual behaviors and functions required for successful cross-cultural management at the strategic and interpersonal level. Includes numerous boxed features that relate concepts to real-world practice. Also includes experiential exercises for self-test. For professionals in international business.